Pohon Industri (Interaktif) Sebagai Pengembangan Layanan Informasi di Perpustakaan PDDI LIPI - Mohamad Djaenudin; Tupan . (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2021)
Abstract(Objectives) The purpose of writing this paper is to explain the process of making industrial trees (interactive) as an information service development activity carried out by the Center for Scientific Data and Documentation (PDDI) which is useful for the community because it provides an overview and stimulates entrepreneurs to carry out and develop product diversification with economic value through the schematic presented. (Method) The stages of making an industrial tree start from topic selection, literature search, article selection and analysis, then proceed with visualization which is then posted on the web.. (Findings) The result of this research showed that audit experience, audit expertise, and locus of control significantly positive affect audit judgment taken by the auditor. Keywords: Information services, Industrial tree (interactive), PDDI LIPI.